1889 Ariz. Sess. Laws 31 - (:unkn) unknown (My University, 1889)
Act of Mar. 18, 1889, no. 13, § 5: Any peace officer who refuses to arrest anyone with the carry on the person, or in saddlebags, of any pistol, dirk, dagger, slung-shot, sword-cane, spear, brass knuckles, Bowie-knife, or any other kind of knife manufactured for purposes of offense or defense shall be punished by fine not exceeding three hundred dollars.
Keywords: PEACE OFFICERS